Growth and Morphogenesis of encapsulated strawberry shoot tips under mixed LEDs - Nguyễn, Văn Kết (Elsevier, 2022)
This study investigated effects of light-emitting diodes (LEDs) with 90% red and 10% blue, 70% red and 30% blue, 50% red and 50% blue, 30% red and 70% blue wavelengths, and fluorescent lamps (control) on in vitro development of encapsulated strawberry shoot tips and their further growth both in vitro and ex vitro. The 90% red and 10% blue LED was optimal for in vitro development. The 70% red and 30% blue LED was effective for both in vitro and ex vitro growth. In comparison with the Control, all LEDs significantly promoted plantlet development and increased survival rate, shoot and root biomass, root number and length, leaf number and area, and chlorophyll content. LEDs can be used as a primary light source for the future commercial applications in asexual propagation of strawberry plants.